Comparison of Three Methods for the Estimation of Pineal Gland Volume Using Magnetic Resonance Imaging - Niyazi Acer; Ahmet Turan Ilıca; Ahmet Tuncay Turgut; Özlem Özçelik; Birdal Yıldırım; Mehmet Turgut (The Scientific World Journal)
Pineal gland is a very important neuroendocrine organ with many physiological functions such as regulating circadian rhythm. Radiologically, the pineal gland volume is clinically important because it is usually difficult to distinguish small pineal tumors via magnetic resonance imaging (MRI). Although many studies have estimated the pineal gland volume using different techniques, to the best of our knowledge, there has so far been no stereological work done on this subject. The objective of the current paper was to determine the pineal gland volume using stereological methods and by the region of interest (ROI) on MRI. In this paper, the pineal gland volumes were calculated in a total of 62 subjects (36 females, 26 males) who were free of any pineal lesions or tumors. The mean ± SD pineal gland volumes of the point-counting, planimetry, and ROI groups were 99.55±51.34, 102.69±40.39, and 104.33±40.45 mm3, respectively. No significant difference was found among the methods of calculating pineal gland volume (P>0.05). From these results, it can be concluded that each technique is an unbiased, efficient, and reliable method, ideally suitable for in vivo examination of MRI data for pineal gland volume estimation.